Recovering Ammonia as Ammonium Citrate and Ammonium Sulfate from Sludge Digestion Liquors Using Membrane Contactors in a Pilot Plant - Ricardo Reyes Alva; Marius Mohr; Günter E. M. Tovar; Susanne Zibek (Membranes)
Membrane contactors have proved to be effective for recovering ammonia from wastewater by absorbing it into a trapping solution. This study compares the performance of sulfuric acid and citric acid as trapping solutions in a pilot-scale plant for recovering ammonia from sludge digestion liquors using membrane contactors in a liquid–liquid configuration operating at pH 10 and a temperature of 37 °C and using ultrafiltration (UF) technology as pretreatment. The performance of the process using sulfuric acid at a lower pH (9.5) and temperature (30 °C) was also studied, as well as the advantage of including a CO2-stripping module in the process. The ammonia elimination efficiency was 88% and 86% when using sulfuric acid and citric acid, respectively. The nitrogen concentration of the produced ammonium sulfate and ammonium citrate reached 23.2 and 14.7 g NH3-N·L−1, respectively. The ammonia elimination efficiency when using sulfuric acid decreased to 49% when decreasing the pH to 9.5 and to 85% when decreasing the temperature to 31 °C. UF technology was able to reduce the concentration of suspended solids by 90% and the chemical oxygen demand by 37%. However, the UF membranes for the pretreatment and the membrane contactors for ammonia recovery had to be constantly cleaned with acid due to scaling, which significantly increased maintenance efforts. The CO2-stripping module reduced the consumption of the caustic soda solution by 23% for increasing the pH level of the treated water. Finally, the specific energy consumption of the plant was 8 kWh·m−3.